1995
DOI: 10.4141/cjas95-015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of embryonic oxygen consumption of two broiler chicken lines differing in body fat content

Abstract: in body fat content were incubated und o*ygen consumption of single embryos was measured on days l4-19 of incubation with an indirect calorimeter. The objectives of this study were to investigate oxygen consumption patterns of the two genetic lines in the late stage of embryonic dlvelopment (days [14][15][16][17][18][19] (Romanoff 1967;Noble and Moore 1964,1966). Also during this time, the rate of protein deposition decreases while the rate of fat deposition increases (Romanoff 1967

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The MRI and image reconstruction technique is also useful for assessing body composition (Scollan et al, 1993), NMR offers a non-invasive, in vivo and sequential approach to monitoring the in uence of genotype (Liu et al, 1995), nutritional and environmental factors on the growth and development of speci c organs and tissues and composition of the body. Until now, the use of NMR in animal studies has been limited, probably because of the low availability of suitable facilities and the high cost of using them.…”
Section: Discussionmentioning
confidence: 99%
“…The MRI and image reconstruction technique is also useful for assessing body composition (Scollan et al, 1993), NMR offers a non-invasive, in vivo and sequential approach to monitoring the in uence of genotype (Liu et al, 1995), nutritional and environmental factors on the growth and development of speci c organs and tissues and composition of the body. Until now, the use of NMR in animal studies has been limited, probably because of the low availability of suitable facilities and the high cost of using them.…”
Section: Discussionmentioning
confidence: 99%
“…Maxwell et al [22] and Witzel [18] concluded that BW at 8 weeks of age was correlated with embryonic O 2 consumption on day 14-19 of incubation. Jones [12] reported an improvement in feed conversion ratio and an increase in BW of 8% when oxygen content within the hatching cabinet was maintained at 23%.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid growth increases the oxygen requirement, cardiac output, and blood flow and may result in increased pulmonary arterial pressure primarily by increasing the metabolic demand for oxygen [14,16,36]. Chicken embryos grow rapidly over the last 7 d of incubation [18] resulting in a 60% increase in the oxygen consumption during the interval between the start of breathing and hatching [34]. Therefore, hypoxia, known to be involved in the occurrence of the ascites syndrome, could arise in the chick embryo during the interval between internal pipping and hatching [8].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, broilers have a high rate of protein accretion [high synthesis and low degradation (Muramatsu et al, 1990)], and it has been shown that fast-growing chickens have relatively larger livers (Konarzewski et al, 2000). On the other hand, layers grow slower but have higher rates of fat deposition, as indicated by the high levels of circulating very low density lipoproteins (Whitehead and Griffin, 1984;Liu et al, 1995), and these traits are pivotal to their high egg productivity. Thus, it is likely that the significant effects on liver embryonic growth observed in domesticated strains indicate that, already at an early age, the embryo is dependent on the capability of the liver to handle metabolic substrates.…”
Section: Brain and Liver Growth Are Differentially Affected By Hypoximentioning
confidence: 99%